Winner’s curse, replication and meta-analysis - Dudbridge, Frank (Henry Stewart Talks, 2016)
Winner's curse: tendency to see a larger effect than usual upon discovery, Examples from GWAS, Methods for obtaining unbiased estimates, Replication: confirming genetic associations in further studies, Technical, direct and indirect replication, Meta-analysis: combining multiple GWAS, Forest plots, fixed and random effects, sources of heterogeneity in GWAS